Problemy zarządzania nieruchomościami - Kisiel, Jerzy (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
In this paper the specific problems of real estates management as a specific economical good are describing. First of all a physical and immaterial aspects of real estates management are conspicuous. On the immaterial aspect the negative limitation of the law property are describing, and the positive aspect of the law property as subjective law. Afterwards the typical tasks of real estates management (administration) are presenting. This tasks are more and more revealing only in the period of economical transformation of polish economic. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1083, s. 755-765